The long-term effects of plasma disc coagulation therapy for cervical disc hernia - Ozcan, Sibel; Muz, Arzu; Taskin, Serhat; Poyraz, Ahmet Kursad; Onal, Selami Ates (Kare Publ, 2021)
Objectives: Recently, plasma disc coagulation therapy (PDCT) has been used in the treatment of lumbar and cervical disc hernia (CDH), but the long-term effects of PDCT have not been well documented. The aim of this study was to assess the long-term effects of PDCT on pain score, disc volume, and patient satisfaction in patients with CDH. Methods: Eighty patients with CDH, who underwent PDCT treatment, were included in the study. The patients demographics and pain scores [visual analog scale (VAS)] were recorded on the baseline and in the 1st, 3rd, 6th, and 12th months after PDCT treatment. We evaluated patient satisfaction and disc volume on the 12th month after PDCT. Results: A statistically significant and time-dependent decrease was determined in VAS score. The initial mean VAS score was 6.5 +/- 0.9, and it decreased to 3.4 +/- 0.2 on the final follow-up (p<0.01). According to magnetic resonance imaging pathology, VAS score after PDCT was higher in patients with an extruded disc when compared to patients with bulging and protruded discs at all times (p<0.05). After 12 months, 50% of the patients were reported as excellent and 8.7% of the patients reported as poor based on the Odom criteria. Disc volume decreased after PDCT treatment in the patients who reported that they were excellent based on the Odom criteria (p<0.01). Conclusion: This study demonstrated that PDCT is a safe, effective, and minimally invasive treatment technique for adequately selected patients with CDH.
Servikal Disk Hernisinde Plazma Disk Koagülasyon Tedavisinin Uzun Dönem Etkileri
Keywords: Cervical disc hernia; disc volume; plasma laser therapy; visual analog scale